Benign Fibrous Histiocytoma of the Conjunctiva. (23rd December 2012) - Ryan, Geoffrey; Glasson, Bill; Foster, Andrew
Abstract : A case is reported on recurrence of a rare conjunctival fibrous histiocytoma (FH) in a 38-year-old man. The lesion was excised and subsequently sent for histopathology and immunostaining resulting in a diagnosis of fibrous histiocytoma (FH). Recurrence was detected 3 months postoperatively requiring a conjunctivosclerokeratomy with cryotherapy and flap. At 6-month followup there was no recurrence detected.